Advanced Polymeric Scaffolds for Stem Cell Engineering and Regenerative Medicine (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Reprint entitled “Advanced Polymeric Scaffolds for Stem Cell Engineering and Regenerative Medicine”, co-edited by Doctor João Carlos Silva and Professor Frederico Castelo Ferreira, brings together a collection of 17 articles (1 editorial, 11 original research papers, and 5 literature reviews) describing the recent, exciting developments of state-of-the-art polymeric biomaterial scaffolds with great potential for stem-cell-based tissue engineering applications. These contributions, received from research groups from all over the world, cover a wide range of topics related to polymeric scaffolds, from novel bioinks for 3D bioprinting, engineered hydrogels for soft tissue repair, and drug delivery systems for anticancer therapies to the optimization of scaffolds’ structural and mechanical properties through the use of additives or following mathematical design and in silico modeling approaches. Overall, this Special Issue provides the readers of Polymers with an outstanding and multidisciplinary compilation of exciting, recent, high-quality articles on the development of advanced polymer scaffolds for regenerative medicine applications, highlighting their potential for the development of more affordable and sustainable personalized therapies.